Morfofisiologia e trocas gasosas do capim Panicum Maximum BRS zuri sob salinidade e lâminas de irrigação - Camilo, Danilo de Araújo (2017)
A challenge in making pasture based production systems feasible is the use of forage species more adapted to different environmental conditions. The objective was to evaluate the growth and morphophysiological responses through the morphogenic and structural characteristics, water use efficiency and gas exchanges of BRS Zuri grass under greenhouse conditions. The experiment was arranged in a randomized block split-plot design. The study was performed in two phases: in experiment I, main plots were composed of salinity levels in water (0.5, 2.0, 4.0 and 6.0 dS m-1) and in the subplots (60, 80, 100 and 120% of the evapotranspiration - ET). Due to the severe effects of salinity levels on development and consequent death of plants at the level of 6.0 dS m-1, the study was continued in experiment II (cycles 3 and 4), where the same design was used and the initial salinity levels were replaced by 0.6; 1.8 and 3.0 dS m-1. Salinity levels of 4.0 and 6.0 dS m-1 caused severe impacts on the development of BRS Zuri cultivar with decrease in growth rates (leaf and stem elongation), leaf size (leaf length, width and area), number of live leaves, tillering, proportion and production of green material (leaves and stems) and increase in the proportion and production of the senescent fraction. At these salinity levels, plants developed adaptation strategies such as reduction of leaf area and increase in leaf appearance rate. Water use efficiency and photosynthetic activity were also compromised under higher salinity. However, gas exchanges were favored at the 4.0 dS m-1 level when under high water availability (irrigation depths of 100 and 120% ET). Water deficit provided by irrigation depth of 60% ET negatively influenced growth and gas exchanges. Higher productivity was obtained in irrigation depth of 120% ET. The cultivar presented growth recovery potential with the reduction of salinity levels up to 3.0 dS m-1 as observed in experiment II. Salinity levels of 4.0 and 6.0 dS m-1 are impracticable for development and maintenance of the BRS Zuri cultivar, as they result in a reduction in the morphophysiological characteristics related to growth and production. BRS Zuri cultivar presents growth recovery potential with the reduction of salinity levels, however, the cumulative effects of salinity compromise the physiological apparatus over time, recommending the maximum levels of 2.0 dS m-1 (experiment I) or 1.8 dS m-1 (experiment II) since maintained under high water availability. The use of the irrigation depth of 80% ET may be feasible under low salinity conditions, since few characteristics were affected under these conditions. Irrigation using 60% ET promotes severe and deleterious effects on the morphophysiological and structural characteristics of the cultivar and, under high salinity these effects are intensified. The evaluation of gas exchanges and leaf chlorophyll index should be carried out with caution, since other factors may influence treatment responses.